Tax Corruption: Legal Loopholes and Criminal Practices by High-Ranking Officials - Polontoh, Herry M; S, Lestari Wulandari (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Tax corruption represents a critical issue that undermines economic stability and public trust, particularly when perpetrated by high-ranking officials. This study addresses the interaction between tax corruption and legal loopholes, highlighting how such gaps in the legal system facilitate criminal practices among powerful individuals.Purposes of the Research: The primary aim of this research is to explore how legal loopholes contribute to tax corruption and to examine the criminal practices of high-ranking officials involved in such activities. The study seeks to understand the systemic issues in tax administration and enforcement that allow these practices to flourish.Methods of the Research: The research employs a mixed-methods approach, combining qualitative analysis through interviews with tax officials and legal experts, with quantitative analysis of case studies involving tax fraud and evasion by high-ranking officials. This methodology provides a comprehensive view of both the legal and practical aspects of tax corruption.Results of the Research: : The findings reveal that significant legal loopholes, coupled with inadequate enforcement mechanisms, create opportunities for high-ranking officials to engage in corrupt practices with minimal repercussions. These corrupt practices undermine public confidence in tax systems and result in considerable revenue losses for the state.Conclusions: The research concludes that addressing tax corruption requires comprehensive legal reforms to close existing loopholes and enhance enforcement capabilities. Strengthening transparency and accountability mechanisms, along with promoting greater public oversight, are essential to mitigating the effects of tax corruption and restoring integrity in tax administration.